2017
DOI: 10.3390/met7080312
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis and Fatigue Life Estimations for Quenched and Tempered Steel at Different Tempering Temperatures

Abstract: Abstract:In this paper, the statistical properties and fatigue life estimations of 0.44% carbon steel at different tempering temperatures are presented. The specimens were austenized at 900 • C for 10 min, quenched in water, tempered at different temperatures, and then machined to the design geometry and average surface roughness of R a = 0.4 µm. The effect of tempering temperature on the fatigue life of 0.44% carbon steel was investigated using 75 fatigue tests, divided into three groups at temperatures 500 •… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…When low alternating stress is applied, the result of the fatigue life (Table 3) at s max ¼ 220 MPa and s max ¼ 240 MPa coincide well with 4. The resulting material constants are brought into the Basquin equation (Equation ( 2)) to obtain the S-N curve [34].…”
Section: Fatigue Studies Of Coated Samplesmentioning
confidence: 99%
“…When low alternating stress is applied, the result of the fatigue life (Table 3) at s max ¼ 220 MPa and s max ¼ 240 MPa coincide well with 4. The resulting material constants are brought into the Basquin equation (Equation ( 2)) to obtain the S-N curve [34].…”
Section: Fatigue Studies Of Coated Samplesmentioning
confidence: 99%
“…Tests were stopped at a maximum fatigue life of 2 × 10 6 cycles, taking into account the recommendations for the number of cycles of the fatigue limit for this type of steel [39]. The full S-N curves (P = 50%) were adjusted with the well-known Basquin formulation in the form N = α•σ β (α and β values in Table 3) commonly used in modern fatigue investigations with quenched and tempered steels as in [40]. In Figure 5 the S-N curves for the different stress ratios are presented, showing a measurable effect of the mean stresses for all the range of fatigue lives: 2 × 10 4 < N < 2 × 10 6 cycles.…”
Section: Fatigue Test Resultsmentioning
confidence: 99%
“…The tempered samples were examined at various temperatures before being air-cooled to eliminate internal stresses and provide the appropriate strength to the revised steel, as well as to obtain a varied microscopic ratio for the aim of examining its influence on fatigue resistance [25]. An arithmetic analysis of Carbon steel with 0.44 percent stress life at different temperatures was demonstrated [26]. Sultan et al [27] concluded that the coldrolled sample had better mechanical characteristics than the received sample.…”
Section: Introductionmentioning
confidence: 99%